2024
DOI: 10.1039/d4ra01634c
|View full text |Cite
|
Sign up to set email alerts
|

Green synthesis of ZnO-TiO2/RGO nanocomposites usingSenna surattensisextract: a novel approach for enhanced anticancer efficacy and biocompatibility

ZabnAllah M. Alaizeri,
Hisham A. Alhadlaq,
Saad Aldawood
et al.

Abstract: The aim of the present study is to enhance the anticancer and biocompatibility performance of TiO2 and ZnO nanoparticles, and, ZnO-TiO2 and ZnO-TiO2/reduced graphene oxide nanocomposites, against two types of human cancer (HCT116) and normal (HUVCE) cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…The peak located near 2350 cm –1 is assigned to the adsorbed water in the samples. The FTIR spectrum of ZnO-TiO 2 exhibits the overlap of the fingerprint regions of both ZnO and TiO 2 , confirming the formation of a nanohybrid . No additional peaks are found in the FTIR spectrum, which indicates that the prepared samples are free of impurities.…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…The peak located near 2350 cm –1 is assigned to the adsorbed water in the samples. The FTIR spectrum of ZnO-TiO 2 exhibits the overlap of the fingerprint regions of both ZnO and TiO 2 , confirming the formation of a nanohybrid . No additional peaks are found in the FTIR spectrum, which indicates that the prepared samples are free of impurities.…”
mentioning
confidence: 88%
“…The FTIR spectrum of ZnO-TiO 2 exhibits the overlap of the fingerprint regions of both ZnO and TiO 2 , confirming the formation of a nanohybrid. 67 No additional peaks are found in the FTIR spectrum, which indicates that the prepared samples are free of impurities. The Raman results shown in Figure 3b indicated that the ZnO-TiO 2 heterojunction could preserve the crystallinity and the vibrational properties of TiO 2 NPs even after the formation of the heterojunction.…”
mentioning
confidence: 99%